Synergistic Antibacterial Activities of Ginger and Lemongrass Essential Oils as an Alternative Prevention to Food-Borne Disease - Sahamastuti, Agnes Anania Triavika; Andre, Andre; Foustine, Shania; Sumarpo, Anton; Hartiadi, Leonny Yulita (Indonesian Journal of Life Sciences, 2019)
Background: Lemongrass and ginger are traditional food ingredients in Asian countries, including Indonesia, Thailand, India, and Malaysia. Although their single essential oil has been assessed for its antibacterial activities, no report has been done for their combination. Material and methods: Our study evaluated single and combination of these herbs for their antibacterial properties against food-borne bacteria E. coli (NEB® catalog No. C2989K), B. subtilis (ATCC 6633), S. typhi (ATCC 14028) and S. aureus (InaCC B4). Essential oil of lemongrass and ginger were obtained by steam distillation and their antimicrobial were evaluated using disk diffusion assay with chloramphenicol as the standard antibiotic. Synergistic activity was assessed using the combination of materials at two or four-fold dilution from their respected MIC value. Results: We confirmed that single lemongrass and ginger essential oils inhibited the bacteria growth with MIC value of about 1-5% and 2.5-5%, respectively. Moreover, their synergism activities were observed when both were mixed at two-fold dilution from their respective MIC. Conclusion: We conclude that the combination of the ginger essential oils and lemongrass essential oils may have potential as a natural preservative to prevent food-borne diseases.